(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suwardi AB, Navia ZI, Harmawan T, Seprianto, Syamsuardi, Mukhtar E. 2022. Diversity of wild edible fruit plant species and their threatened status in the Aceh Province, Indonesia. Biodiversitas 23: 1311-1319. Aceh Province, Indonesia is home to a diverse range of tropical fruit plants. However, increased anthropogenic activities such as population growth and natural disasters resulted in various biological resources such as wild edible fruit plants being under threat. The study aimed to assess the diversity and threatened status of wild edible fruit plant species in the Aceh Province of Indonesia. The study was conducted in six regencies, namely Aceh Tamiang, Aceh Timur, Aceh Selatan, Aceh Utara, Aceh Barat, and Aceh Tengah. At each study area, a line transect of 1,000 meters was laid from the forest’s edge into the forest. Wild edible fruit plant species discovered along the transect were collected and given local names. A total of 129 wild edible fruit plant species at six studied areas in the Aceh Province belonged to 38 families. The highest number of fruit plant species was recorded in the district of Aceh Tamiang, i.e., 63 species, followed by Aceh Selatan (56 species), Aceh Barat (46 species), Aceh Timur (37 species), Aceh Utara (31 species), and Aceh Tengah (23 species). Mangifera foetida Lour., Mangifera odorata Griff., Artocarpus integer (Thunb.) Merr., Ficus altissima Blume, Ficus fistulosa Reinw. ex Blume, Syzygium cumini (L.) Skeels, Passiflora foetida L., and Pometia pinnata J.R. Forst. & G. Forst. were the most frequently recorded wild fruit plant species in all regencies. From 129 wild edible fruit species recorded in the study areas, 35% are currently classified as Least Concern, 6% as Vulnerable, 3% as Near Threatened, 2% as Low Risk, 2% as Data Deficient, and 52% of species in the IUCN red list had No Available Data. Community-based conservation through domestication of wild edible fruit plant species can be one of the management strategies for the conservation of wild edible fruit plants in Aceh Province.